An RGD Helper Sequence in CagL of Helicobacter pylori Assists in Interactions with Integrins and Injection of CagA - Conradi, Jens; Tegtmeyer, Nicole; Woźna, Marta; Wissbrock, Marco; Michalek, Carmela; Gagell, Corinna; Cover, Timothy L.; Frank, Ronald; Sewald, Norbert; Backert, Steffen (Frontiers in Cellular and Infection Microbiology, 2012)
Helicobacter pylori is a specific gastric pathogen that colonizes the stomach in more than 50% of the world’s human population. Infection with this bacterium can induce several types of gastric pathology, ranging from chronic gastritis to peptic ulcers and even adenocarcinoma. Virulent H. pylori isolates encode components of a type IV secretion system (T4SS), which form a pilus for the injection of virulence proteins such as CagA into host target cells. This is accomplished by a specialized adhesin on the pilus surface, the protein CagL, a putative VirB5 ortholog, which binds to host cell β1 integrin, triggering subsequent delivery of CagA across the host cell membrane. Like the human extracellular matrix protein fibronectin, CagL contains an RGD (Arg-Gly-Asp) motif and is able to trigger intracellular signaling pathways by RGD-dependent binding to integrins. While CagL binding to host cells is mediated primarily by the RGD motif, we identified an auxiliary binding motif for CagL-integrin interaction. Here, we report on a surface-exposed FEANE (Phe-Glu-Ala-Asn-Glu) interaction motif in spatial proximity to the RGD sequence, which enhances the interactions of CagL with integrins. It will be referred to as RGD helper sequence (RHS). Competitive cell adhesion assays with recombinant wild type CagL and point mutants, competition experiments with synthetic cyclic and linear peptides, and peptide array experiments revealed amino acids essential for the interaction of the RHS motif with integrins. Infection experiments indicate that the RHS motif plays a role in the early interaction of H. pylori T4SS with integrin, to trigger signaling and to inject CagA into host cells. We thus postulate that CagL is a versatile T4SS surface protein equipped with at least two motifs to promote binding to integrins, thereby causing aberrant signaling within host cells and facilitating translocation of CagA into host cells, thus contributing directly to H. pylori pathogenesis.